Volume Measurement in the Diagnosis of Mounier Kuhn Syndrome and an Unknown Accompanying Pathology: Pulmonary Artery Enlargement - Aktaş, Fatma; Aktaş, Turan (Current Medical Imaging, 2019)
Background: Mounier Kuhn Syndrome (MKS) is a rare congenital anomaly characterized by abnormal dilatation of the trachea and main bronchi. The aim of this study is to discuss tracheal volume measurement in MKS, and the pathologies accompanying MKS, especially pulmonary artery enlargement. Materials and Methods: 38 patients, 18 of whom were diagnosed with MKS and 20 as control group, were included in the study. Trachea volume and pulmonary artery diameter were measured through thorax-computed tomography (CT) images of the patients. Accompanying pathologies were recorded. Results: In the measurements done through the CT scans, the trachea volume was found to be 25.45 cm3 in the control group and 44.17 cm3 in the patient group. The most frequent accompanying pathologies were tracheal diverticulum, bronchiectasis and pulmonary artery enlargement. Conclusion: In patients with MKS, there is a significant difference in volume calculation as in trachea diameter. Though bronchiectasis and tracheal diverticulum are known as pathologies most frequently accompanying MKS, to the knowledge of the researchers, pulmonary artery enlargement due to the increase in pulmonary truncus diameter was first emphasized in this article.
Keywords: volume calculation